Avaliação do efeito anti-inflamatório da dexametasona e do cetorolaco em exodontias de terceiros molares inferiores - Oliveira, Janayna Gomes Paiva (2012)
The objective of this randomized, double-blind, cross-over, was to compare the efficacy of dexamethasone 8 mg and 10 mg ketorolac tromethamol, through the assessment of pain, swelling and trismus. The comparison of anti-inflammatory effects of dexamethasone (steroid) and ketorolac tromethamol (NSAIDs) has not been held in separate groups used in isolation. Therefore, 30 individuals of both genders, aged 18 to 26 years without local or systemic diseases, and has held bilateral lower third molars, in a similar position, were selected and underwent surgery to remove it. Two separate sessions were held by the same operator and separated by a minimum of 21 days. For extraction, the subject received a tablet of ketorolac tromethamol 10 mg orally 1 hour before surgery and every 8 hours for 2 days. For the extraction operated on the opposite side, the same individual received one tablet of dexamethasone 8 mg orally 1 hour before the start of surgery and a placebo tablet every 8 hours for 2 days. Tablets of sodium dipyrone 500 mg were given a drug to escape analgesia. Pain was assessed by visual analogue scale of 11 points in cash within 24 hours after surgery. Edema (metric measurement) and maximum mouth opening (interincisal) were recorded in the pre - operative, 24, 48, 72 hours and 7 days after surgery. The results showed that both drug treatments used were effective in third molar surgery retained, and for the variables pain and swelling there was no statistically significant differences between groups. However, to trismus in 24 hours and 7 days postoperative dexamethasone group had a lower limitation of mouth opening, behaving, therefore, better than ketorolac for this variable during these periods.